Selecting the right branded management company - Larone, David (Henry Stewart Talks, 2009)
What does a brand offer?, Franchise versus management contract, What comes first in the decision process?, Identifying product niche, New builds and conversions, Capital cost, Brand support, Brand portfolio, Key aspects of owner/manager relations, Who owns the asset?, Negotiating management contracts, Budget preparation, Intellectual property, Personnel of the hotel, Selling one's asset